Perancangan Smart Packaging Intip dengan Menggunakan Metode Kansei Engineering dan Eco-Design(Studi Kasus: Industri Pembuatan Intip Wilayah Kota Surakarta) - Muttaqin, Eko Dwi, Ahmad Kholid Al Ghofari, ST. MT (2016)
Intip is one of the local wisdom that must be maintained the existence. One of the efforts made to preserve the existence of intip is with innovative products and its called PIEMIRSA intip (Pie Intip Rasa-rasa) by adding new flavors apart originally consisted of salty and sweet taste of sugar to 18 flavors. Product innovation alone is not enough, innovation must also be viewed from the aspect of marketing because the conditions intip is fragile and only use plastics that are particularly at risk when it should be marketed in the distance. Based on these problems made smart packaging for intip attention to aesthetics, functionality, strength and provide a positive image for the product and the environment. Design of Smart Packaging is done by the method of Kansei Engineering and eco-design. Kansei method step is the collection of consumer preferences of packaging in the form of adjectives, test the adequacy of the data, the validity reliability test, factor analysis, determination of items and categories of items, conjoint analysis through SPSS Software, and determines the design concept and specifications based on test results conjoint. The concept of eco-design used to produce packaging that is sustainable. Besides the calculation of Cost of Production (HPP) HPP Smart Packaging and PIEMIRSA after use the Smart Packaging. Based on the obtained results and discussion of design specifications Smart Packaging with a beam shape, small size, natural color, as well as made from bamboo that is sustainable. Besides the concept of eco-design is applied to the use of notice / warning in the form of solicitation implementation of sustainable systems. HPP Smart Packaging obtained based on the result of the calculation is Rp 6.850,00 / unit and HPP PIEMIRSA using Smart Packaging Rp 20.254,00 / unit.